Importance of radon assessment in indoor Environment-a review. (2022) - Gopalakrishnan, Preethi; Jeyanthi, J.
Abstract: Radon is odourless, colourless indoor air pollutant from the radiation source of uranium. The source of radon in indoor are walls, floor and ceiling. Importance of radon detection at buildings are rare as it cannot be suspected until faced with an health issues. Concentration of radon in indoor environment depends on various factors. Lund disorders are the most commonly reported issue with radon exposure. This paper concentrates on the sources, factors influencing the radon dispersion and the health issues rise up with high radon exposure.